Indole fragments for the design of lead molecules against pancreatitis. Issue 1 (2nd January 2020) - Dileep, K. V.; Ashok, S.; Remya, C.; Dharmendra, K. Y.; Pérez-Sánchez, Horacio; Sadasivan, C.
Abstract: Communicated by Ramaswamy H. Sarma